Phase behavior of ASDs based on hydroxypropyl cellulose - Christian Luebbert; Edmont Stoyanov; Gabriele Sadowski (Elsevier, 2021)
Novel polymeric carriers for amorphous solid dispersions (ASDs) are highly demanded in pharmaceutical industry to improve the bioavailability of poorly-soluble drug candidates. Besides established polymer candidates, hydroxypropyl celluloses (HPC) comes more and more into the focus of ASD production since they have the availability to stabilize drug molecules in aqueous media against crystallization. The thermodynamic long-term stability of HPC ASDs with itraconazole and fenofibrate was predicted in this work with PC-SAFT and compared to three-months enduring long-term stability studies. The glass-transition temperature is a crucial attribute of a polymer, but in case of HPC hardly detectable by differential scanning calorimetry. By investigating the glass transition of HPC blends with a miscible polymer, we were for the first time able to estimate the HPC glass transition. Although both, fenofibrate and itraconazole reveal a very low crystalline solubility in HPC regardless of the HPC molecular weight, we observed that low-molecular weight HPC grades such as HPC-UL prevent fenofibrate crystallization for a longer period than the higher molecular weight HPC grades. As predicted, the ASDs with higher drug load underwent amorphous phase separation according to the differential scanning calorimetry thermograms. This work thus showed that it is possible to predict critical drug loads above which amorphous phase separation and/or crystallization occurs in HPC ASDs.